Die klingende Ferne; Walter Braunfels' Opera Die Vögel after Aristophanes' Birds. (12th August 2019) - Ewans, Michael
Abstract: This article explores the opera Die Vögel (1920) by Walter Braunfels (1882–1954), and its reception of Aristophanes' Birds . The Introduction is substantial, as the work is little known. It is followed by an Overview of each of the two Acts, which discusses in Act I the relationship to Aristophanes (Braunfels discarded the second half of the original Greek comedy and struck out on a completely new path). Then the article analyses the development during Act II of insight into die klingende Ferne ('the music of far away') by Hopeful, who is the principal human character in Braunfels' adaptation. It is shown that Hopeful's quest for spiritual values almost beyond human understanding is the central theme of the opera; the superiority of the life of birds, which Aristophanes treats humorously in the two parabaseis, is taken seriously in Braunfels' mystical second Act.